Cycles versus trends: The effects of economic growth on earnings in Bolivia - Beatriz Muriel Hernández; Horacio Vera Cossio (Institute for Advanced Development Studies (INESAD), 2015)
This paper analyzes the effects of economic growth on labor earnings in Bolivia during 1999-2012. More precisely, we develop a labor market model to capture both cycle and trend effects of prices, and production on earnings, which is estimated econometrically using pseudo-panel data methods. The results show that labor earnings have had a pro-cyclical behavior. In particular, we find that, in the short run, an increase of 1% in prices or production explains an earnings rise of around 0.5%, while, in the long run, a production increase of 1% is associated with an earnings variation of 0.4%. Furthermore, we find that labor earnings growth by sector follows, to some extent, the economic performance of its corresponding sector, which responds to the sector segmentation characteristics in the Bolivian labor market.
Keywords: E29; E32; J29; J39; J42; 330; Bolivia; earnings; wages; economic growth; business cycle; pseudo-panel